Applying Lessons from Maine’s Educational Opportunity Tax Credit to the Student Loan Repayment Tax Credit - Acheson-Field, Hannah (Maine Policy Review, 2023)
In 2008, Maine implemented the Educational Opportunity Tax Credit (EOTC), a tax credit available to eligible recent college graduates with student debt. The share of eligible filers who apply for and receive the EOTC has been relatively low, however, likely driven by a lack of awareness about the program and its complicated application processes and eligibility criteria. In April 2022, the legislature created the Student Loan Repayment Tax Credit (SLRTC), which simplifies some of these processes. Meeting the legislature’s goals for this program, however, may require expanding awareness of the SLRTC and ensuring that the application process is simple. This article provides information and analysis about implementation of the EOTC with comparisons to the SLRTC.
Keywords: EOTC; SLRTC; student loan debt